Faktor-Faktor Yang Mempengaruhi Kualitas Hidup Pasien Gagal Ginjal Kronik Yang Mendapatkan Hemodialisis Di Rumah Sakit Pekanbaru Medical Center: Factors that influence the quality of life of patients with chronic renal failure who get hemodialysis at Pekanbaru Medical Center Hospital - Galaresa, Achmad Vindo (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Hemodialysis can extend life without a clear limit, this action will not change the natural course of kidney disease and also will not restore all kidney function. This study aims to determine the factors that influence the quality of life of patients with chronic renal failure who get hemodialysis at Pekanbaru Medical Center Hospital. The design of this study was cross-sectional design. This study was conducted in a hemodialysis room with 30 respondents. The sampling method used was purposive sampling. The measuring instrument used is a questionnaire that has been tested for validity. The analysis used is the Chi-square test. The results showed that the underlying disease factors affected the quality of life of patients receiving hemodialysis (p-value = 0,003), comorbid conditions (p-value = 0,002), medical management factors (p-value = 0,014), and distance to health facilities (p-value = 0,003). The results of this study are expected to be used as input for the hospital to pay more attention to patients' quality of life with chronic renal failure which can improve the quality of service that is caring and facilitate patient comfort in therapy.